2013
DOI: 10.1017/s1368980013002607
|View full text |Cite
|
Sign up to set email alerts
|

Development of a competency framework for the nutrition in emergencies sector

Abstract: Objective: There is a recognised need to strengthen capacity in the nutrition in emergencies sector and for greater clarity on the role of emergency nutritionists and the skills they require. Competency frameworks are an important tool for human resource development and have been developed for several other humanitarian sectors. We therefore developed a technical competency framework for practitioners in nutrition in emergencies. Design: Existing competency frameworks were reviewed and interviews conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…These curricular recommendations for graduates in the nutrition field align with previously published recommendations ( 13 , 31 , 32 ). Although the workshop highlighted content area requirements for formal and informal training programs, it did not specify competencies of individual graduates in each instance.…”
Section: Discussionsupporting
confidence: 81%
“…These curricular recommendations for graduates in the nutrition field align with previously published recommendations ( 13 , 31 , 32 ). Although the workshop highlighted content area requirements for formal and informal training programs, it did not specify competencies of individual graduates in each instance.…”
Section: Discussionsupporting
confidence: 81%
“…Eleven papers were published between 2005 and 2011 [ 26 , 28 – 30 , 32 , 33 , 37 – 41 ] and eight published between 2012 and 2016 [ 11 , 25 , 27 , 29 , 31 , 34 – 36 ]. Five of the papers were published in Canada [ 27 , 28 , 34 , 35 , 38 ], five in the United States [ 26 , 30 , 37 , 40 , 41 ], two in Australia [ 24 , 33 ], two in Europe [ 29 , 31 ] and one in the United Kingdom [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five of the papers were published in Canada [ 27 , 28 , 34 , 35 , 38 ], five in the United States [ 26 , 30 , 37 , 40 , 41 ], two in Australia [ 24 , 33 ], two in Europe [ 29 , 31 ] and one in the United Kingdom [ 39 ]. Four of the papers did not state a specific country [ 11 , 25 , 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meeker, et al (2013) examined nutrition in emergencies, using core competency frameworks as well as course curricula, job descriptions and interviews.…”
Section: Specific Sector Competenciesmentioning
confidence: 99%
“…This is also apparent in other contexts; Sansom and Coates (2011) identified management (functional) competencies that relate specifically to urban water supply. KovĂĄcs et al (2012) and Meeker et al (2013) also demonstrated that the non-humanitarian specific competencies for logisticians and nutritionists working in other (non-humanitarian) contexts do not provide the level of guidance required for an emergency logistician or nutritionist, although Meeker et al (2013) did note communality between humanitarian and development contexts. Engineering is similar, with many (but not all) aspects of, say, sanitation, being common to disasters and development, but not to stable, developed contexts.…”
Section: Specific Sector Competenciesmentioning
confidence: 99%